Teknik Massage Counterpressure Berpengaruh Terhadap Penurunan Nyeri Kala I Fase Aktif Pada Ibu Bersalin - Wardiyaningtuti, Nuning; Indriati, Ina; Retnaningsih, Reny (Universitas Tribhuwana Tunggadewi, 2023)
During labor, pain can lead to hyperventilation, increasing oxygen demand and blood pressure while reducing intestinal motility and bladder function. This situation triggers the release of catecholamines, potentially interfering with uterine contractions and causing uterine inertia, leading to prolonged labor. To address this, a pre-experimental study using a one-group pretest-posttest design was conducted among 30 birth mothers from the Rejoso Health Center, Pasuruan Regency. The study employed total sampling, and data analysis utilized the Independent sample t-test to evaluate the impact of counterpressure massage techniques on pain reduction during the first active phase of labor. The research revealed a significant effect, indicated by a p-value of 0.004 0.05, demonstrating the effectiveness of counterpressure massage in reducing pain during the initial active phase of labor for women in the Rejoso Health Center area. Consequently, it is recommended that laboring women experiencing pain be offered the counterpressure massage technique